Me Rev. Stat. tit. 12, ch. 164, § 4 (1841) - (:unkn) unknown (My University, 1834)
If any person shall carry on the business of manufacturing gun powder, or of mixing or grinding the composition therefor, in any building within eighty rods from any valuable building, erected at the time when such business may be commenced the building, in which such business may be carried on as aforesaid, shall be deemed a public nuisance; and such person shall be liable to be prosecuted and indicted accordingly.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER